Bismuth-Centered Radical Species: Access and Applications in Organic Synthesis - Martínez, Sebastián; Lichtenberg, Crispin (Synlett, 2023)
Recent advances in the isolation of tamed bismuth radicals and the selective in situ generation of highly reactive bismuth radicals have set the stage for the application of these compounds in organic and organometallic synthesis and catalysis. Here, we provide a summary of the methodological approaches in the field. Important strategies for accessing bismuth radical species are presented and key examples of their applications in organic synthesis are outlined, highlighting how this class of compounds has emerged as new set of valuable tools for synthetic practitioners.1 Introduction2 Generation of Bismuth Radical Species by Homolysis2.1 Temperature-Induced Homolysis2.2 Light-Induced Homolysis2.3 Light-/Temperature-Induced Bi–C Homolysis of Polar Oxidative Addition Complexes3 Applications of Bismuth-Centered Radical Species in Organic Synthesis3.1 Bismuth-Catalyzed Cycloisomerization of Iodo Olefins3.2 Controlled Radical Polymerization Reactions3.3 Bismuth-Promoted Pn–Pn and C–S Coupling3.4 Bismuth-Catalyzed Dehydrocoupling of Silanes with TEMPO3.5 Bismuth-Catalyzed C–N Coupling with Redox-Active Electrophiles3.6 Bismuth-Catalyzed Giese-Type Coupling Reactions3.7 Oxidative Addition of Aryl Electrophiles to Photoactive Bismuthinidenes4 Conclusions
Keywords: bismuth radicals; bismuth catalysis; C–X coupling (X = B, C, N, S); light-induced radical formation; temperature-induced radical formation